켄터키블루그래스의 봄철 그린업을 위한 해조추출물과 칼륨의 늦가을 시비 효과 - 이상국(Sang-Kook Lee) (Weed & turfgrass science, 2022)
식물은 겨울철 휴면기간과 봄철 휴면기에서 벗어나는 시기에 발생하는 다양한 피해를 예방하기 위해 품종개발, 잔디피복재 사용, 식물생장조절제 등 다양한 방법을 사용한다. 해조추출물은 다량원소 및 미량원소를 포함하고 있을뿐 아니라 다양한 식물호르몬을 포함하고 있어 잔디관리에 있어 식물생장조절제로서 많이 사용되고 있다. 칼륨(potassium, K)은 여러가지 환경스트레스 환경하에 있는 식물의 스트레스 저항성 향상에 효과가 있는 것으로 알려져 있다. 본 실험에서는 늦가을 Kentucky bluegrass에서 칼륨의 시비와 해조추출물 처리 조합이 낮은 온도의 동절기 피해기간에 대한 내한성 향상과 봄철 그린업 성장률에 대해 어떤 효과를 나타내는지 검증하기 위해서 수행되었다. 해조추출물 0, 1, 2, 4, 8 mL m-2의 비율과 칼륨시비량을 위해 황산칼륨(potassium sulfate, 0-0-50)이 0, 10, 20, 40 g K2O m-2의 비율로 처리되었다. 잔디엽색과 품질 잔디피복률에서 지상부 적정생육온도 범위보다 낮은 환경에서는 해조추출물과 칼륨의 효과가 나타났다. 해조추출물 4 mL m-2 농도는 가장 높은 잔디엽색과 잔디피복률을 나타냈으며, 칼륨시비량 10 g m-2 은 가장 높은잔디엽색, 잔디품질, 잔디피복률을 나타냈다. 그러나 그 이상의 높은 농도에서는 잔디품질과 잔디피복률에서 대조구와차이가 나타나지 않아 그 효과가 없는 것으로 판단된다. Seaweed extracts have been used to improve resistance ability to drought and cold temperature because they contain a wide range of minerals and plant hormones such as abscisic acid, auxins, betaines, cytokinins, and gibberellins. Potassium (K) is well-known for one of the essential nutrients that also increase cold resistance of plants. Although increasing cold resistance by seaweed extracts and K have been reported, research results about interactions between seaweed extracts and K applications to Kentucky bluegrass for cold resistance are limited. The objective of this study was to evaluate seaweed extracts and K rates as late fall application for spring green-up of Kentucky bluegrass. The seaweed extracts at rates of 0, 1, 2, 4, and 8 mL m-2 are applied and potassium sulfate (0-0-50) as K sources was applied at the rate of 0, 10, 20, 40 g K2O m-2. There are significant differences among seaweed extracts and K rates for turfgrass color, quality, and turf coverage under the optimum air temperature range for cool-season grasses. Overall, the seaweed extracts of 4 mL m-2 had the greatest turf color and turf coverage and the K rate of 10 g m-2 had the greatest turf color, turf quality, and turf coverage. The higher rate of seaweed extracts than 4 mL m-2 and K rate than 10 g m-2 had no difference with control for turf quality and turf coverage. KCI Citation Count: 0